Late contained aortic root rupture and ventricular septal defect after transcatheter aortic valve implantation1. Issue 1 (4th May 2012) - Aminian, Adel; Lalmand, Jacques; Dolatabadi, Dariouch
Abstract Transcatheter aortic valve implantation (TAVI) is a highly specialized technique offering a new therapeutic option to patients at high risk for conventional surgery. However, despite continuous improvements in operators' expertise and device technology, complications associated with this catheter procedure are not uncommon. We report an unusual case of late contained rupture of the aortic annulus, combining a para‐aortic false aneurysm and a ventricular septal defect, after the placement of an Edwards Sapien prosthesis. © 2012 Wiley Periodicals, Inc.